TRANSITIVITY ANALYSIS OF EFL STUDENTS’ NARRATIVE TEXT IN VOCATIONAL HIGH SCHOOL - Agustina, Maria; Suarnajaya, Wayan (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
Language cannot be understood one at a time without considering contextual information about the current circumstances and culture. As a result, language can only be understood when individuals comprehend the circumstance and culture. This study aimed at identifying the process types that characterize the students' narrative texts. This study applied a descriptive qualitative method. The researcher collected the data from narrative texts. There were 28 students selected to be the subjects of this study. The collected data, presented in sentences and clauses, were analyzed using Halliday's transitivity system. Findings show that the process type that are dominantly used in the students' narrative texts are material, behavioral, intensive attributive, verbal, mental, and existential processes. The material process was the most common process type used because the students' subjects were connected to past figures. The findings in this study of the students' narrative texts demonstrate that the students must use the linguistic elements of a narrative text to give information. The purpose of text types in students' narrative texts is to encourage readers to imagine the words and sentence patterns used in the texts. It may help to minimize misunderstandings about the contents of the narrative text. As a result, while creating a narrative text, the students must employ the proper specific meaning, generic structure, linguistic characteristics, and language elements to stimulate readers' interest in providing necessary information while entertaining them.